Gender, power and identity : essays on masculinities in rural North India - Prem Chowdhry (Orient Blackswan, 2019)
As the discipline of gender studies has almost become synonymous with women’s studies, men and masculinities are subsumed under patriarchy/ies and constructed as monolithic across space, time, cultures and social groups. Though men’s studies have proliferated in Western academia, in India the research in this direction is lacking. Neither is there a coherent theory of masculinities, nor individual studies of different regions.